2022
DOI: 10.1038/s41598-022-08150-y
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the effects of decontamination treatments on the structural and functional integrity of N95 respirators via numerical simulations

Abstract: Filtering facepiece respirators (FFRs) provide effective protection against diseases spread through airborne infectious droplets and particles. The widespread use of FFRs during the COVID-19 pandemic has not only led to supply shortages, but the disposal of single-use facemasks also threatens the environment with a new kind of plastic pollution. While limited reuse of filtering facepiece respirators has been permitted as a crisis capacity strategy, there are currently no standard test methods available for dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Further details of Geodict based analysis can be obtained from ref. [31]. In general, the porosity values of control and decontaminated samples obtained via CTAn and Geodict analyses are in good agreement.…”
Section: X-ray Microcomputed Tomography Analysismentioning
confidence: 69%
“…Further details of Geodict based analysis can be obtained from ref. [31]. In general, the porosity values of control and decontaminated samples obtained via CTAn and Geodict analyses are in good agreement.…”
Section: X-ray Microcomputed Tomography Analysismentioning
confidence: 69%
“…Once the microorganisms were trapped in the fi lter, approximately 1% of the inoculated bacteria were recovered in the buff er solution, and the exact decontamination capacity of each method was unclear. However, other in-vitro studies have demonstrated that many methods tested in this study have effi cient decontamination capacity against viruses and bacteria, including M. tuberculosis [12,[17][18][19]. However, the microorganism trapping capacity of the N95 respirator is high and may not release the captured microorganisms from the fi bre fi ltration system.…”
Section: Discussionmentioning
confidence: 84%
“…These results indicate that in comparison with the traditional melt-blown microfibrous membranes with randomly distributed fibers, the microfibrous membranes with a fluffy alignment structure exhibit excellent and controllable air-penetration properties. 42…”
Section: Resultsmentioning
confidence: 99%